Analysis and Evaluation of Financial Performance Using inancial Indicators An Applied Study at Arcelor Mittal Annaba, 2014)-Algeria (2013 - Zaibet, Nour addin; Hattab, Dallel (Milev Journal of Research and Studies, 2018)
The research aims to demonstrate the importance of analyzing and evaluating the financial performance of Arcelor Mittal Steel Annaba, based on the financial indicators to analyze the financial performance, including the liquidity ratios, financial balance indicators, and cost indicators. We used the analytical descriptive method to suit the research topic and the results obtained. The financial indicators have shown that the financial position of the institution is short term in the short term. The main recommendations of the research are the need to control the costs of all types.